2020
DOI: 10.31436/ijpcc.v6i2.147
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the adoption of e-commerce by Small and Medium-Sized Enterprises (SMEs) in Algeria: a qualitative study

Abstract: Small and Medium-sized Enterprises (SMEs) are regarded as the engine of the growth of the world economy. They had recently experienced rapid growth and improved their business activities in terms of customers’ number and revenue expansion when they began to embrace e-commerce and started using it in their business. However, although there is a growing interest in e-commerce, its use is still insufficient in Algeria. Therefore, this study aimed to identify the factors that influence the adoption of e-commerce b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The utilization of social media appears to be impacted by two key factors: testability and observability. Previous research has identified significant connections between testability and the propensity to embrace e-commerce [33], as well as between observability and the desire to adopt cloud technologies [34]. These findings highlight the influence of these factors on the adoption of different technological platforms.…”
Section: Discussionmentioning
confidence: 70%
“…The utilization of social media appears to be impacted by two key factors: testability and observability. Previous research has identified significant connections between testability and the propensity to embrace e-commerce [33], as well as between observability and the desire to adopt cloud technologies [34]. These findings highlight the influence of these factors on the adoption of different technological platforms.…”
Section: Discussionmentioning
confidence: 70%
“…Hajli et al [36] identified barriers to e-commerce in Iran, such as a lack of awareness of its benefits and organizational issues related to its implementation. Hassen [37] conducted a qualitative study on factors influencing the adoption of e-commerce by SMEs in Algeria and found that electronic payment methods, banking readiness, legal protection, awareness of e-commerce benefits, and risk concerns were the main barriers.…”
Section: Literature Reviewmentioning
confidence: 99%